Steering from bismarck to beveridge: the french experience - Philippe Mossé (Universidade de Fortaleza, 2018)
Objective: To describe the roots of the French Health Care System. Data synthesis: Actually, three dynamics are hidden behind the word crisis. The first dynamic was already there from the start, while the second is the result of an internal dynamic and a third dynamic can be seen as the consequence of external causes. The main recent policies are made of a mix of constraints and incentives. Most of them improve the governance of the health care system. Adaptive as well as innovative, a pragmatic attitude has been applied through compromises. Four features of which can be found: To improve the division of labor amid professionals; to move towards Beveridge like Welfare State model, giving to the central State more power; to enhance expertise through Evidence Based Medicine; to open the internal and external frontiers of the health care system. Conclusion: Those changes were mainly pulled by the moving context rather than pushed by an ideology. Therefore, since its birth, the French health care system evolves more on a muddling through like move than according to a plan given in advance. This happened to be a rather good way to avoid the worst: marketization.